Assessment of Phytochemical, FT-IR and GC-MS Fingerprint Profiling of Marine Angiosperms Enhalus acoroides (L.f) Royle and Syringodium isoetifolium (Asch) Dandy, Gulf of Mannar Biosphere Reserve, Tamil Nadu - Selvam, Murugeswaran Santhiya; Tresina, Pious Soris; Benjamin, Jeben; Mohan, Veerabahu Ramasamy (Asian Journal of Biological and Life Sciences)
Objectives: Seagrasses, the marine angiosperm plants, grow in saline environments. Fully submerged in the sea, they are widely distributed along the Gulf of Mannar biosphere reserve regions of Tamil Nadu. The current study was carried out to evaluate the possible bioactive components, present in seagrasses Enhalus acoroides and Syringodium isoetifolium. Methodology : Petroleum ether, benzene, ethyl acetate, methanol, ethanol and aqueous extracts were subjected to qualitative test for the identification of phytoconstituents as per standard procedure. The functional groups of plant powder were identified using FTIR analysis. The ethanol extraction were analyzed via GC-MS techniques. Results: The presence of catechin, flavonoid, phenol, saponin, tannin and glycoside is revealed through the phytochemical screening of the diverse solvent extracts of E. acoroides and S. isoetifolium. The Fourier Transform-Infra Red (FT-IR) spectroscopy analysis confirmed the presence of hydroxyl, phenolics/alcohol, alkane, ester, ether, amine and others. The Gas Chromatography-Mass Spectrum (GC-MS) analysis showed the presence of each ten phytocompounds including n-Hexadecanoic acid, phytol, stigmasterol, hexadecanoic acid and methyl ester. Conclusion: The analyses proved the presence of important bioactive compounds with medicinal properties in the marine angiosperms found in the Gulf of Mannar biosphere reserve regions of Tamil Nadu. The therapeutic effects of seagrasses were the results of the presence of bioactive components in them.
Keywords: Flavonoids; FT-IR; GC-MS; Marine angiosperm; Phytochemical; Stigmasterol and Phytol